IMPLEMENTASI KEBIJAKAN PAJAK KENDARAAN BERMOTOR DALAM MEMAKSIMALKAN PENDAPATAN ASLI DAERAH (STUDI PADA UPT SAMSAT BALARAJA) - Fatmawati, Sarah; Murodi, Ahmad; Badar, Refly (Jurnal Ilmu Administrasi Negara (JUAN), 2022)
Policy implementation has a legal basis that applies so that a common goal can be achieved during the implementation of the policy implementation. The process of developing certain areas requires large costs and the details of expenditure requirements are clear. In the implementation of financial management, the regional government gives authority to the Regional Revenue Agency (BAPENDA). One source of local revenue is motor vehicle tax. The implementation of the collection is regulated in Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. This study aims to examine the implementation of motor vehicle tax policies in maximizing local revenue at UPT SAMSAT Balaraja, Tangerang Regency. The method used in this study is a qualitative research which in the implementation of data collection carried out observations of the research location, interviews with several sources, and documentation. The results of this study indicate that the implementation of the motor vehicle tax policy has been going very well with the support of 3 services outside the UPT SAMSAT Balaraja and 3 special programs that have been approved by the heads of agencies from BAPENDA, POLRI, and PT. Jasa Raharja